2018
DOI: 10.2478/lpts-2018-0034
|View full text |Cite
|
Sign up to set email alerts
|

First-Principles Modelling of N-Doped Co3O4

Abstract: N-doped Co3O4 is a promising electrocatalyst. By means of first-principles calculations, various concentrations and spatial arrangements of NO atoms were modelled. Mutual interaction of the dopant atoms was analysed with respect to single NO atom. Charge redistribution, caused by doping, was calculated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Core electrons were substituted with Ultra Soft (US) potentials with the Projector Augmented Wave (PAW) method (Kresse and Joubert, 1999). Computational parameters were carefully tested in previous computational studies on the N-doped Co 3 O 4 bulk (Kaptagay et al, 2018) and surface (Kaptagay et al, 2020). Exchange-correlation was described by the PBE functional (Perdew et al, 1996).…”
Section: Methods and Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Core electrons were substituted with Ultra Soft (US) potentials with the Projector Augmented Wave (PAW) method (Kresse and Joubert, 1999). Computational parameters were carefully tested in previous computational studies on the N-doped Co 3 O 4 bulk (Kaptagay et al, 2018) and surface (Kaptagay et al, 2020). Exchange-correlation was described by the PBE functional (Perdew et al, 1996).…”
Section: Methods and Modelmentioning
confidence: 99%
“…Earlier computational studies revealed that N o is stable in the Co 3 O 4 bulk (Kaptagay et al, 2018) as well as on a Co 0.5 -terminated (001) surface (Kaptagay et al, 2020). Exploiting the models developed in these studies, we simulated OER on a N-doped Co 3 O 4 surface.…”
Section: Introductionmentioning
confidence: 99%